Transformation of Post-Mining Landscapes into Tourism: A Local-Driven Initiative in Loa Ulung, East Kalimantan - Hanif, Salma Nur; Winoto, Yunus; Muslim, Dicky (International Journal of Science and Society, 2025)
The legacy of coal mining in East Kalimantan, Indonesia, has left numerous degraded landscapes, including abandoned pit lakes that pose significant environmental and social challenges. Amidst these issues, local communities in Desa Loa Ulung have initiated a transformation, repurposing this former mining pit lake into tourism destinations. This article aims to examine the planning and implementation processes undertaken by these local initiatives. Employing a qualitative case study design, data were collected through in-depth interviews, direct observation, and document analysis with key local initiators and managers. The analysis reveals that the planning process is predominantly organic and adaptive, driven by strong social capital and personal initiatives, often navigating a void in formal legal status. This informal framework enables flexible, bottom-up innovation but also presents challenges related to incremental resource mobilization, limited infrastructure, and fragmented spatial layouts. The findings highlight how community-driven approaches reframe degraded lands into valuable assets, offering critical insights into adaptive development strategies in post-extractive contexts. This study underscores the importance of understanding local dynamics for fostering resilient and community-led transformations of challenging landscapes.